Single step synthesis and properties of M/MFe2O4 and PVDF/M/MFe2O4 (M = Co, Ni) magnetic nanocomposites - Deka, Sasanka; Joy, Pattayil Alias; Kumar, A. Pratheep (Science of Advanced Materials, 2009)
Metal/ferrite nanocomposites (M/MFe2O4; M = Co, Ni), consisting of nanoparticles of a metal and the corresponding metal ferrite, have been synthesized under in situ conditions by a simple and single step process. The metal/ferrite nanocomposites embedded in a polymer matrix have been prepared by a simple hot-pressing method. The performance parameters such as magnetization, coercivity, permeability and dielectric constant of the two- and three-phase nanocomposite systems are compared. The coercivity increases and the permeability decreases with increasing polymer content in the three-phase composite. Enhancement of the dielectric constant is observed at low frequencies.
Keywords: Dielectric; Ferrite; magnetic properties; Nanocomposite; Nanocrystalline; permeability